The Influence of E-Service Quality and Customer Experience against Repurchase Intention and Trust as the Intervening Variable - Fachrullah, Muhammad; Permana, Dudi (ARE Publisher, 2024)
Objectives: The research of this study is to aim and determine to analyze the effect of E Service Quality and Customer Experience on Repurchase Intention with Trust as a mediating variable. Methodology: This research data is taken from the primary data obtained from processing questionnaire data filled out by the Tokopedia users who have made at least two purchases. The number of samples used was 108 respondents and the analysis technique used in this study is to use the partial least square (Pls) analysis. Finding: The results of this study indicate that trust mediates the relationship between e service quality variables and customer experience on repurchase intention which has a positive and signiicant effect Conclusion: The results of hypothesis testing show that E-Service Quality has a positive and significant effect on Trust, Customer Experience has a positive and significant effect on Trust, Trust has a positive and significant effect on Repurchase Intention, E-Service Quality has a positive and insignificant effect on Repurchase Intention, Customer Experience has a positive and insignificant effect on Repurchase Intention, Trust has a positive and significant effect on mediating the E-Service Quality variable on Repurchase Intention, Trust has a positive and significant effect on mediating the Customer Experience variable on Repurchase Intention.